Analyzing the Influence of Modic Changes on Patients with Lower Back Pain Undergoing Conservative Treatment - Yufeng Chen; Huilin Yang; Lianfang Zhang; Yue Wang; Jun Zou (Pain Research and Management)
Objective. This study aimed to investigate if the presence of Modic changes (MCs) was correlated with lower back pain (LBP) and LBP-related disability in patients who underwent nonsurgical treatment. Methods. In this study, 129 patients who experienced consecutive LBP and underwent lumbar spine magnetic resonance imaging in our institute were divided into three groups according to the presence or type of MCs. The Oswestry Disability Index (ODI) and visual analog scale (VAS) were used to assess the outcomes of the treatment. Results. Based on the achieved results, there was no significant difference between three groups before treatment (P>0.05). Three months after undergoing nonsurgical treatment, the rates of improved ODI and VAS scores were statistically significantly different (P=0.014,  0.023). After an additional 3 months of treatment, in patients with Modic type I changes, the symptoms significantly improved in comparison with those 3 months prior (P=0.037,  0.026), while that improvement did not occur in patients with Modic type II changes (P>0.05). Conclusions. The existence of MCs affects the outcomes of nonsurgical treatment in patients with LBP. However, symptoms can be improved after an additional round of treatment for Modic type I changes, while this is not confirmed for Modic type II changes.